Development Of Smart Apps Creator Interactive Learning Media With Augmented Reality (AR) Containing Water Cycle Material For Grade V Elementary School - Zilda Kurnia Sektiyana; Dewi Nilam Tyas; Siti Maryatul Kiptiyah (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: The water cycle topic in IPAS learning is often perceived as abstract and difficult to understand by elementary school students. To address this issue, this study aims to develop, validate, and evaluate the effectiveness of an interactive learning media based on Smart Apps Creator with Augmented Reality (AR) to improve the learning outcomes of fifth-grade students. The research method used is Research and Development (R&D) with a simplified Borg & Gall model, consisting of nine stages, from problem identification to large-scale testing. Expert validation showed that the media was highly feasible, with average scores of 92.5% from media experts and 94% from subject matter experts. Normality tests confirmed that the data were normally distributed, while the Paired T-Test indicated significant differences between pretest and posttest results (p = 0.019 for the small group and p = 0.000 for the large group). The N-Gain scores were 0.6281 (small group) and 0.5812 (large group), both falling into the moderately effective category. These results indicate that the Smart Apps Creator-based media with AR is feasible and effective in enhancing students’ understanding of the water cycle concept and improving their academic performance in fifth-grade science classes. Abstrak: Materi siklus air dalam pembelajaran IPAS sering dianggap abstrak dan sulit dipahami oleh siswa sekolah dasar. Untuk mengatasi tantangan ini, penelitian ini bertujuan mengembangkan, menguji kelayakan, dan mengevaluasi efektivitas media pembelajaran interaktif berbasis Smart Apps Creator bermuatan Augmented Reality (AR) dalam meningkatkan hasil belajar siswa kelas V SD. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model Borg & Gall yang disederhanakan menjadi sembilan tahap, mulai dari identifikasi masalah hingga uji coba skala besar. Validasi oleh pakar menunjukkan media sangat layak dengan skor rata-rata 92,5% (pakar media) dan 94% (pakar materi). Uji normalitas membuktikan data berdistribusi normal, sedangkan uji Paired T-Test menunjukkan perbedaan signifikan antara pretest dan posttest (p = 0,019 untuk kelas kecil dan p = 0,000 untuk kelas besar). Uji N-Gain menghasilkan skor 0,6281 (kelas kecil) dan 0,5812 (kelas besar), yang termasuk kategori cukup efektif. Hasil tersebut menunjukkan bahwa media berbasis Smart Apps Creator dengan AR dinyatakan layak dan efektif dalam membantu pemahaman konsep siklus air serta meningkatkan hasil belajar siswa kelas V SD.